2020
DOI: 10.1097/aog.0000000000004160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fasting on Total Bile Acid Levels in Pregnancy

Abstract: OBJECTIVE: To evaluate differences between fasting and nonfasting bile acid levels in asymptomatic and symptomatic pregnant women. METHODS: This is a report of two prospective cohort studies describing bile acid levels in the fasting and nonfasting state in pregnancy. The first cohort included asymptomatic women with singleton pregnancies. Women with a diagnosis of cholestasis, symptoms of cholestasis, or intolerance to components of a standardized meal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Our study confirms that TSBA levels increase in response to food intake and that differences between fasting and postprandial measurements are clinically and statistically significant 11,29 .…”
Section: Main Findingssupporting
confidence: 84%
See 4 more Smart Citations
“…Our study confirms that TSBA levels increase in response to food intake and that differences between fasting and postprandial measurements are clinically and statistically significant 11,29 .…”
Section: Main Findingssupporting
confidence: 84%
“…It has recently been suggested that higher thresholds should be used for the diagnosis of ICP, also given the low risk of stillbirth demonstrated recently for TSBA levels < 100 μmol/L 26,29 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations